Deliberative democracy as a tool to foster youth participation in Europe: the case of Citizens’ Juries in Sierra Norte - Soto-Sainz, Óliver (Frontiers in Political Science, 2025)
Since the late 1970s, there has been a general trend toward a decline in electoral participation in European democracies. That tendency is especially acute if we refer to young people, who find no means to carry their demands to the public authorities. This downward trend in citizen participation in elections has occurred at the same time that European countries have experienced an overall increase in the socioeconomic level and educational background of the population, factors traditionally associated with greater electoral participation. This constant decline, together with other processes, has led to this situation being described as a “crisis of representative democracies.” To alleviate this crisis, many countries have proceeded to use innovative formulas to try to incorporate citizens into decision-making processes. On the one hand, the advance in communication technologies is allowing not only greater access to information, but also increasing the possibilities of both direct interaction with citizens and the ability to respond to simple demands. On the other hand, a part of the population increasingly demands that their proposals be taken into consideration, not only as a democratic right, but also as a tool for more effective management. In this article, we explore the implementation of two specific experiences at the local level with young people, evaluating their impact in small towns in Sierra Norte and the challenges they present for municipalities that wish to implement them in a post-pandemic context. We present the methodology used to conduct them and the main findings that might help to reproduce these initiatives.